Pengembangan Keterampilan Bernyanyi Mahasiswa Difabel Nonfisik melalui Pelatihan Musik di Art Therapy Center Widyatama - Reffali, Soni; Yully Hidayah; Siti Khumairo (LPPM ISBI Bandung, 2024)
Abstract This study aims to describe the process and outcomes of singing skill training for non-physical disabled students at the Art Therapy Center Widyatama. The research used a descriptive qualitative method, with observation and interviews as the main data collection techniques. The study found that the singing skill training was conducted through several stages, including basic technique introduction, singing practice, and performance evaluation. Despite some challenges during the training process, such as difficulties in adapting to the learning methods, the results show that students were able to significantly develop their vocal skills. These findings support the importance of adapting teaching methods to meet the specific needs of disabled students to maximize their potential in the field of music arts. Keywords: singing training, non-physical disabilities, music, arts education, adaptive teaching